Model and Non-model Insects in Chronobiology - Beer, Katharina; Helfrich-Förster, Charlotte (Frontiers in Behavioral Neuroscience, 2020)
The fruit fly Drosophila melanogaster is an established model organism in chronobiology, because genetic manipulation and breeding in the laboratory are easy. The circadian clock neuroanatomy in D. melanogaster is one of the best-known clock networks in insects and basic circadian behavior has been characterized in detail in this insect. Another model in chronobiology is the honey bee Apis mellifera, of which diurnal foraging behavior has been described already in the early twentieth century. A. mellifera hallmarks the research on the interplay between the clock and sociality and complex behaviors like sun compass navigation and time-place-learning. Nevertheless, there are aspects of clock structure and function, like for example the role of the clock in photoperiodism and diapause, which can be only insufficiently investigated in these two models. Unlike high-latitude flies such as Chymomyza costata or D. ezoana, cosmopolitan D. melanogaster flies do not display a photoperiodic diapause. Similarly, A. mellifera bees do not go into “real” diapause, but most solitary bee species exhibit an obligatory diapause. Furthermore, sociality evolved in different Hymenoptera independently, wherefore it might be misleading to study the social clock only in one social insect. Consequently, additional research on non-model insects is required to understand the circadian clock in Diptera and Hymenoptera. In this review, we introduce the two chronobiology model insects D. melanogaster and A. mellifera, compare them with other insects and show their advantages and limitations as general models for insect circadian clocks.